Nacella EDGARI - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Nakano, Tomoyuki; Saucède, Thomas; Spencer, Hamish; Poulin, Elie (Zenodo, 2018)
NACELLA EDGARI (POWELL, 1957) (FIG. 11) Patella ( Patinella ) fuegiensis – Smith, 1879: 180, pl. 19, figs 14, 14a (not of Reeve). Nacella fuegiensis – Pilsbry, 1891: 121, pl. 49, figs 28, 29, 30, 31 (not of Reeve). Nacella ( Patinigera ) fuegiensis – Thiele, 1912: 234 (not of Reeve). Patinigera fuegiensis edgari Powell, 1957: 127, pl. 2, figs 5, 6; Powell, 1960: 129. Nacella ( Patinigera ) edgari – Powell, 1973: 196, pl. 179, figs 3, 4; Cantera & Arnaud, 1985: 35; Troncoso et al. , 2001: 88. Nacella ( Patinigera ) macquariensis – Powell, 1973: 196 (in part, not of Finlay). Nacella cf. macquariensis – González-Wevar et al. , 2010: 116 (not of Finlay). Nacella edgari – González-Wevar et al. , 2016b: 2; 2017: 862. Material studied: Port-aux-Français, Kerguelen Islands (49°21’09.84’’ S, 70°13’05.89’’ E) N = 40; Port Christmas, Kerguelen Islands (48°41’40.22’’ S, 69°01’15.54’’ E) N = 50; Fjord des Portes Noires, Kerguelen Islands (49°29’47.32’’ S, 69°08’06.70’’ E) N = 30; Îles du Prince-de-Monaco, Kerguelen Islands (49°36’47.24’’ S, 69°14’11.38’’ E) N = 50; Baie des Cascades, Kerguelen Islands (49°10’02.31’’ S, 70°08’53.33’’ E) N = 30; Atlas Cove, Heard Islands (53°01’27.99’’ S, 73°23’46.95’’ E) N = 5. Shell: The shell shape and sculpture are variable in the species and two different morphologies were recorded at Kerguelen (Fig. 11A, B) and Heard Islands (Fig. 11C), respectively. Individuals from the Kerguelen Islands exhibit a conical morphology, dorsally depressed, with a thin and translucent shell. The anterior part of the animal is laterally compressed (Fig. 11D–F). The shell is of medium size (maximum length 80 mm) and has a low profile. The apex is located at the anterior 20–30% of the shell. All the slopes of the shell are concave. The aperture is oval. The whole surface is crowded with concentric lamellae that undulate as they cross the radials. The margin of the shell is very crenulated. The external coloration varies in the species across its distribution (brown, grey and purple) and the apex has a bronze coloration. The interior part of the shell is iridescent bluish grey with dark lines, corresponding to external colour patterns bordered by a white/grey halo. The morphology of N. edgari at Heard Island was relatively constant in the analysed individuals ( N = 5) with a conical form, dorsally raised, very thick and not translucent. The anterior part of the animal is laterally compressed. The shell is of medium size (maximum length 80 mm) and has a medium profile. The apex is situated at the anterior 30–40% of the shell’s length. All the slopes of the shell are convex. The aperture of the shell is oval. The surface of the shell consists of low radial folds and lamellar growth lines. The margin of the shell is very crenulated. External coloration varies from brown to reddish. The internal part of the shell has iridescent bluish grey coloration with dark lines corresponding to external colour patterns bordered by a white/grey halo. External anatomy: The ventral area of the foot is black and the epipodial fringe is highly recognizable. The mantle fold is thick and dun-brown coloured. The mantle tentacles are in alternate series of three white shorter and a white longer one and are absent of pigmentation (Fig. 11G). The cephalic tentacles are dorsally pigmented with a black line (Fig. 11G). Radula: The first lateral teeth are set close together on the anterior edge of the basal plates, of medium length and sharp pointed, with two cusps. The second laterals are broader, wider spaced with four short cusps (Fig. 11H). Distribution: Kerguelen and Heard Islands (Fig. 11I). Habitat: This species occurs from high and medium intertidal rocky shores down to 30-m depths; the species is also regularly found on macroalgae (Powell, 1955, 1957) Comments: In the original description of the radula from Kerguelen Islands individuals (under the name Patella fuegiensis ) Smith (1879) describes: Teeth of the lingual ribbon slightly hooked, in pairs, scarcely diverging; the central pairs twopronged, the inner prong much the larger, spearhead shaped; the lateral pairs alternating with the central ones are four-pronged, the innermost prong smallest, the next two subequal, and the outside one situated nearly at right angles to the rest of the tooth, about the same size or a trifle larger. This radular teeth configuration highly resembles our observations of the radula of N. edgari . At the same time, the lateral and dorsal patterns of shell morphology recorded in Patella fuegiensis from Kerguelen by Smith (1879) are very similar to those observed in N. edgari . Accordingly, individuals identified as Nacella fuegiensis from Kerguelen should be treated as N. edgari . Powell (1957) commented that the adults of N. edgari have a very thin and fragile shell, and live closely associated to ‘kelps’. Recent multi-locus reconstructions indicate that N. edgari from the Kerguelen Islands and N . cf macquariensis from Heard Island (González-Wevar et al. , 2010) represent the same evolutionary unit (González- Wevar et al. , 2017). Moreover, Nacella individuals from Macquarie Island fell within a different and endemic lineage, N. macquariensis , closely related to N. edgari (Kerguelen and Heard Islands) and to N. terroris (Campbell Island). Therefore, the colonization of both sub-Antarctic Australia / New Zealand islands, Macquarie and Campbell, constitutes a recent off-shoot from a geographically distant Kerguelenian Nacella lineage. Accordingly, N. edgari is currently restricted to Kerguelen and Heard Islands where, it coexists with N. kerguelenensis . : Published as part of González-Wevar, Claudio A., Hüne, Mathias, Rosenfeld, Sebastián, Nakano, Tomoyuki, Saucède, Thomas, Spencer, Hamish & Poulin, Elie, 2019, Systematic revision of Nacella (Patellogastropoda: Nacellidae) based on a complete phylogeny of the genus, with the description of a new species from the southern tip of South America, pp. 303-336 in Zoological Journal of the Linnean Society 186 on pages 322-325, DOI: 10.1093/zoolinnean/zly067, http://zenodo.org/record/5718878 : {"references": ["Powell AWB. 1957. Mollusca of Kerguelen and Macquarie Islands. B. A. N. Z. Antarctic Research Expedition, 1929 - 1931. Report B 6: 107 - 149.", "Smith EA. 1879. Mollusca. An account of the petrological, botanical and zoological collection made in Kerguelen's Island and Rodriguez during the Transit of ' Venus' Expedition in the years 1874 - 75. Philosophical Transactions of the Royal Society of London 168: 167 - 192.", "Pilsbry HA. 1891. Manual of conchology. Structural and systematic with illustrations of the species, Vol. 13. Philadelphia, PA: Academy of Natural Sciences.", "Thiele J. 1912. Die antarktischen Schnecken und Muscheln. Deutsche Sudpolar-Expedition (1901 - 1903) 13: 183 - 285.", "Powell AWB. 1960. Antartic and subantartic mollusca. Records of the Auckland Institute and Museum 5: 117 - 193.", "Powell AWB. 1973. The patellid limpets of the World (Patellidae). In: Abbot RT ed. Indo-Pacific Mollusca: monographs of the marine mollusks of the world with emphasis on those of the tropical western Pacific and Indian Oceans, Vol. 3. Auckland, New Zealand: Auckland Institute and Museum.", "Cantera JR, Arnaud PM. 1985. Les gasteropodes prosobranches des Iles Kerguelen et Crozet (Sud de L'Ocean Indien) comparison ecologique et particularites biologiques. CNFRA (Comite National Francais des Recherches Antarctiques) 56: 1 - 169.", "Troncoso N, Van Goethem JL, Troncoso JS. 2001. Contribution to the marine molluscan fauna of Kerguelen Islands, South Indian Ocean. Iberus 19: 83 - 114.", "Gonzalez-Wevar CA, Nakano T, Canete JI, Poulin E. 2010. Molecular phylogeny and historical biogeography of Nacella (Patellogastropoda: Nacellidae) in the Southern Ocean. Molecular Phylogenetics and Evolution 56: 115 - 124.", "Gonzalez-Wevar CA, Hune M, Rosenfeld S, Saucede T, Feral J-P, Mansilla A, Poulin E. 2016 b. Patterns of genetic diversity and structure in Antarctic and sub-Antarctic Nacella (Patellogastropoda: Nacellidae) species. Biodiversity 17: 46 - 55.", "Gonzalez-Wevar CA, Hune M, Segovia NI, Nakano T, Spencer HG, Chown S, Saucede T, Johnstone G, Mansilla A, Poulin E. 2017. Following the Antarctic Circumpolar Current: patterns and processes in the biogeography of the limpet Nacella (Mollusca: Patellogastropoda) across the Southern Ocean. Journal of Biogeography 44: 861 - 874.", "Powell AWB. 1955. Mollusca of the Southern Islands of New Zealand. Cape Expedition Series Bulletin N \u00b0 15. Wellington, New Zealand: Department of Scientific and Industrial Research."]}